STUDI EMPIRIS TERHADAP FAKTOR YANG MEMPENGARUHI PILIHAN KARIR MAHASISWA AKUNTANSI - Sekar Kuningsih, Reni; Harto, Puji (Diponegoro Journal of Accounting, 2013)
This study aims to examine the differences on job expectation on whether students choose to pursue a public accountant career or nonpublic- accouuntant career.This research took a sample of 129 respondents from final year of undergradute accounting students (S1), Professional Program in Accounting (PPA) students, and Master Degree (S2) students. The data was collected by distributing questionnaire to respondents directly. The data was analyzed using exploratory factor analysis.The result of this study indicated that there were significant differences on job expectation between students choose to pursue a public accountant career and students choose to pursue nonpublic-accountant career.